Emerging Electroencephalographic Biomarkers to Improve Preclinical to Clinical Translation in Alzheimer’s Disease - Cope, Zackary A.; Murai, Takeshi; Sukoff Rizzo, Stacey J. (Frontiers in Aging Neuroscience, 2022)
Continually emerging data indicate that sub-clinical, nonconvulsive epileptiform activity is not only prevalent in Alzheimer’s disease (AD) but is detectable early in the course of the disease and predicts cognitive decline in both humans and animal models. Epileptiform activity and other electroencephalographic (EEG) measures may hold powerful, untapped potential to improve the translational validity of AD-related biomarkers in model animals ranging from mice, to rats, and non-human primates. In this review, we will focus on studies of epileptiform activity, EEG slowing, and theta-gamma coupling in preclinical models, with particular focus on its role in cognitive decline and relevance to AD. Here, each biomarker is described in the context of the contemporary literature and recent findings in AD relevant animal models are discussed.